PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2024 - Diah Permata Sani Simanullang; Robinhot Gultom; Dimita H.P. Purba (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine and analyze the influence of Capital Structure, Firm Size, and Institutional Ownership on Financial Performance in Consumer Non Cyclicals Sector Companies, specifically the Food and Beverage Sub-Sector listed on the Indonesia Stock Exchange for the Period 2021-2024. The independent variables in this study are Capital Structure measured by Debt to Equity Ratio (DER), Firm Size measured by Natural Logarithm of Total Assets, and Institutional Ownership (IO), while the dependent variable is financial performance measured using Return on Assets (ROA). This study employs a quantitative approach with multiple linear regression analysis method. The sample in this study was obtained using purposive sampling method. The data used are secondary data obtained from financial statements of companies listed on the IDX. Based on the established criteria and data processing, 42 companies were determined as the research sample. The results of this study indicate that partially Capital Structure has a significant negative effect on Financial Performance, while Firm Size has a negative and insignificant effect on financial performance. Institutional Ownership has a positive and significant effect on Financial Performance. Simultaneously, Capital Structure, Firm Size, and Institutional Ownership have a significant effect on Financial Performance.